(untitled) - Perreault, William D (United States, 2010)
This book is about marketing and marketing strategy planning. And, at its essence, marketing strategy planning is about figuring out how to do a superior job of satisfying customers. This author team takes that point of view seriously and believes in practicing what they preach. Your customers can trust that this new edition of Essentials of Marketing 12e– and all of the other teaching and learning materials that accompany it – will satisfy your customers’ needs.
Keywords: Marketing,Tiếp thị